Mortality in mental health patients of the Emilia–Romagna region of Italy: A registry-based study. (February 2021) - Berardi, Domenico; Stivanello, Elisa; Chierzi, Federico; Musti, Muriel Assunta; Perlangeli, Vincenza; Pandolfi, Paolo; Piazza, Antonella; Saponaro, Alessio; Sanza, Michele; Ferri, Mila; Menchetti, Marco; Fioritti, Angelo
Highlights: The mortality gap it is mainly due to natural deaths. The mortality gap regards both severe mental illnesses and milder conditions. Depressed patients could be at greater risk of dying from cancer. Personality disorders need monitoring for cardiovascular disease. Abstract: Evidence from previous research demonstrated a gap in mortality between patients with mental disorders and the general population. However, a more exhaustive assessment is required to address this public health issue. The aim of this study was to provide comprehensive analysis of mortality examining all causes of death and all psychiatric diagnoses. We conducted a 10-year retrospective cohort study, including all in and out patients registered in the Mental Health Registry of Emilia-Romagna, Italy. Standardized mortality ratios (SMRs) were calculated. The cohort consisted of 137, 351 patients 11, 236 of whom died during the study period and the overall SMR was 1.99. 85.9 % of excess mortality was attributable to a broad range of natural causes. Diseases of circulatory and respiratory systems as well as neoplasms were the principal contributors to the mortality gap. All psychiatric conditions led to a higher risk of death. The greatest excess was due to neoplasms in depressed and neurotic patients and to cardiovascular diseases in patients with schizophrenia and personality disorders. Our results highlight the need for close collaboration between mental and primary health care services with the aim of reducing excess mortality as a result of medical diseases among all patients suffering from psychiatric condition.